IDENTIFIKASI VANCOMYCIN RESISTANT Staphylococcus aureus (VRSA) PADA MEMBRAN STETOSKOP DI RUMAH SAKIT MARGONO SOEKARJO PURWOKERTO - Darmawan, Anton Budi; Anjarwati, Dwi Utami (MANDALA of Health, 2010)
Vancomycin-resistant Staphylococcus aureus (VRSA) was first discovered in 2002 by a clinician inthe USA. Vancomycin resistance mediated by the van gene which will result in a change in the terminalS.aureus cell wall. Data on epidemiology of VRSA from RSUD Margono Soekarjo (RSMS), Purwokertogenerally were not available. The purpose of the study was identify VRSA on stethoscopes membrane inRSUD Margono Soekarjo (RSMS), Purwokerto. A Laboratory observational study with cross sectionaldesign was conducted to 69 stethoscopes membrane in RSUD Margono Soekarjo (RSMS), Purwokerto.Isolates were taken from stethoscopes membrane for Vancomycin discs testing to detect VRSA. The resultshowed that 10 of 64 isolates with S.aureus positive (15,6%) found on stethoscopes membrane were VRSA.In conclusion, VRSA was found on stethoscopes membrane in RSUD Margono Soekarjo (RSMS),Purwokerto.